Oligodendrogenesis is a key process for cognitive performance improvement induced by voluntary physical activity. Issue 6 (1st February 2022) - Eugenin von Bernhardi, Jaime; Dimou, Leda
Abstract: Physical activity (PA) promotes the proliferation of neural stem cells and enhances neurogenesis in the dentate gyrus resulting in hippocampal circuit remodeling and cognitive enhancement. Nonetheless, knowledge of other neural progenitors affected by PA and the mechanisms through which they could contribute to circuit plasticity and cognitive enhancement are still poorly understood. In this work we demonstrated that NG2‐glia, also known as oligodendrocyte progenitor cells, show enhanced proliferation and differentiation in response to voluntary PA in a brain region‐dependent manner in adult mice. Surprisingly, preventing NG2‐glia differentiation during enhanced PA abolishes the exercise‐associated cognitive improvement without affecting neurogenesis or baseline learning capacity. Thus, here we provided new evidence highlighting the requirement of oligodendrogenesis for exercise induced‐cognition enhancement. Main Points: Voluntary physical activity leads to the increase of oligodendrogenesis selectively in the motor cortical grey matter. Block of oligodendrogenesis abolishes the enhancement of cognitive performance induced by running without affecting neurogenesis.